Evolution of human mitochondrial DNA variations - Kivisild, Toomas (Henry Stewart Talks, 2021)
Origins of mitochondria in our cells, Functional role, size, and copy number of mitochondria, Inheritance of mitochondrial genes, Mitochondrial mutation rate, Haplotypes and haplogroups, Geographic distribution of mtDNA diversity in humans, Natural selection and dispersals in shaping mtDNA variation, Residence pattern effect on mtDNA diversity